Is there a therapeutic or pharmacokinetic rationale for amphotericin B dosing in systemic Candida infections? - Nagata, M P; Gentry, C A; Hampton, E M (The Annals of pharmacotherapy, 1996)
To review the literature regarding the dosage of amphotericin B in Candida infections. The correlation or rationale of current dosing practices is assessed in light of the literature. A MEDLINE search encompassing the years 1968-1995 was used to identify pertinent literature. Additional references were obtained from the articles retrieved from MEDLINE. Studies that directly assessed amphotericin B dosage and/or duration, pharmacokinetic literature dealing with plasma concentrations and amphotericin B disposition, and literature dealing with dose and/or concentration as well as clinical outcome were selected for inclusion. Additional relevant citations were used in the introductory material and discussion. Although there was a large number of articles related to amphotericin B, surprisingly few large studies were designed to address the issues in question. The description of the methods and results of these heterogeneous articles are the basis of this review. Although additional controlled studies with more subjects need to be performed, the results to date provide a foundation from which to make some inferences regarding optimal use of this therapeutic modality until more definitive data become available. Despite numerous articles addressing the pharmacokinetics of amphotericin B, little is known about its tissue distribution, the rate of transfer of the drug from vascular to peripheral sites, or its terminal disposition. Less information is available regarding the relevance of pharmacokinetic parameters or serum concentrations to clinical outcome. Most of the articles mentioning dosing provide little or no justification for the doses employed. The variety of the dosages used and the heterogeneity of the populations studied make determination of dose-outcome relationships difficult. From the available clinical data, it appears that early initiation of amphotericin B therapy is crucial to a favorable outcome. Daily dosing initially followed by every-other-day administration of twice the daily dose is better tolerated by the patient than daily dosing and produces a similar therapeutic outcome. The drug should be continued until therapeutic endpoints have been achieved, rather than until a specific total dosage has been administered. The nephrotoxicity that occurs with amphotericin B administration is apparently reversible and should not be used as an endpoint for therapy if total dosages do not exceed 4 g. Additional well-designed, controlled trials evaluating standardized dosing methods of amphotericin B with predetermined dosing regimens and/or definitive therapeutic endpoints are needed to determine the optimal dosing approach for this agent.